ISO 9001:2015 and Capability Maturity Model Integration 3.0 in Software Development Project - Fariz, Achmad Arzal; Raharjo, Teguh; Genia, Venera (AI Society & STMIK Indonesia, 2023)
Integration between Capability Maturity Model Integration (CMMI) 3.0 and ISO 9001 can provide several significant benefits to organizations seeking to improve the quality, efficiency, and maturity of their processes. CMMI and ISO 9001 can be integrated framework as guidance and evaluation. ISO 9001 promotes a risk-based approach, while CMMI helps in measuring process capability. Literature review conducted between 2018-2023 that indicates five researches regarding ISO 9001 and CMMI for software development. This study aims to integrate the ISO 9001:2015 standard with the CMMI 3.0 model. Selected CMMI 3.0 Practice Area PLAN, EST, CM, RDM, SAM, PQA, and MC are mapped in clause 8, while only RSK is mapped in clause 6. This study can be developed by mapping other Practice Area of CMMI and other standard.